A Skin‐Interfaced, Miniaturized Microfluidic Analysis and Delivery System for Colorimetric Measurements of Nutrients in Sweat and Supply of Vitamins Through the Skin. Issue 2 (7th November 2021) - Kim, Joohee; Wu, Yixin; Luan, Haiwen; Yang, Da Som; Cho, Donghwi; Kwak, Sung Soo; Liu, Shanliangzi; Ryu, Hanjun; Ghaffari, Roozbeh; Rogers, John A.
Abstract: Nutrients play critical roles in maintaining core physiological functions and in preventing diseases. Technologies for delivering these nutrients and for monitoring their concentrations can help to ensure proper nutritional balance. Eccrine sweat is a potentially attractive class of biofluid for monitoring purposes due to the ability to capture sweat easily and noninvasively from nearly any region of the body using skin‐integrated microfluidic technologies. Here, a miniaturized system of this type is presented that allows simple, rapid colorimetric assessments of the concentrations of multiple essential nutrients in sweat, simultaneously and without any supporting electronics – vitamin C, calcium, zinc, and iron. A transdermal patch integrated directly with the microfluidics supports passive, sustained delivery of these species to the body throughout a period of wear. Comparisons of measurement results to those from traditional lab analysis methods demonstrate the accuracy and reliability of this platform. On‐body tests with human subjects reveal correlations between the time dynamics of concentrations of these nutrients in sweat and those of the corresponding concentrations in blood. Studies conducted before and after consuming certain foods and beverages highlight practical capabilities in monitoring nutritional balance, with strong potential to serve as a basis for guiding personalized dietary choices. Abstract : This paper introduces a soft, skin‐interfaced microfluidic system that enables nutrient analysis in sweat and delivery of vitamins to the body. Accurate colorimetric sensors can quantify the concentrations of nutrients in sweat, and a transdermal patch integrated directly with the microfluidics supports passive, sustained delivery of nutrients to the body throughout a period of wear.